So You Want to Quit Smoking : Have You Tried a Mobile Phone? - Labonne, Julien; Chase, Robert S. (World Bank, Washington, DC, 2012)
Tobacco use, which is rising quickly in developing countries, kills 5.4 million people a year worldwide. This paper explores the impacts of mobile phone ownership on tobacco consumption. Indeed, mobile phone ownership could affect tobacco consumption because individuals might pay for their communication with money they would have spent on tobacco. Using panel data from 2,100 households in 135 communities of the Philippines collected in 2003 and 2006, the analysis finds that mobile phone ownership leads to a 20 percent decline in monthly tobacco consumption. Among households in which at least one member smoked in 2003, purchasing a mobile phone leads to a 32.6 percent decrease in tobacco consumption per adult over the age of 15. This is equivalent to one less pack of 20 cigarettes per month per adult. The results are robust to various estimation strategies. Further, they suggest that this impact materializes through a budget shift from tobacco to communication.